Antibacterial activity of Thymus phenols by direct bioautography - Horváth, Gy. (Acta Biologica Szegediensis, 2002)
Planar chromatography is a powerful technique for separating certain classes of compound of biological interest. In higher plants there are many substances which have antimicrobial effect. Bioautography is a method to localize antibacterial activity on a chromatogram. Thymol and carvacrol have antibacterial effect against Erwinia amylovora and Erwinia carotovora. Rosmarinic and caffeic acids were detected in some Thymus taxa but have no antibacterial activity with direct bioautography.